(untitled) (Journal of Mining and Metallurgy, Section B: Metallurgy, 2018)
In this study, magnetizing roasting in fluidized bed was employed to separate iron minerals from red mud. The effect of treatment conditions on product quality was investigated. In addition, the phase transformation, magnetism changes and microstructure were studied by thermodynamic analysis, chemical analysis, X-ray diffraction technique (XRD), vibrating sample magnetometer (VSM) and optical microscopy. Magnetic concentrates with total iron grade of 57.65% and recovery 90.04% were obtained under the optimum conditions. XRD and chemical analysis demonstrated that 92% iron minerals in red mud converted to magnetite. VSM further confirmed that the magnetism of roasting products was strongly enhanced, the specific susceptibility increasing from 1.9×10-5 m3/kg to 2.9×10-4 m3/kg after magnetizing roasting. Fluidized magnetizing roasting is an effective technology for recovering iron minerals from high-iron red mud.